PV & Zeta Converter based Irrigation Pumping System using PMBLDC Motor - et. al., Mukesh Kumar Kumawat , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes an idea of designing & implementing a simple, affordable, productive & pollution free water pumping system using the advantageous features of a zeta converter and PMBLDC motor for the irrigation which will help the farmers in minimizing their farming hurdles which in turn will improve the productivity as well as quality of life. It presents an outstanding system consisting of PMBLDC motor which is fed from a renewable source i.e, from PV array & to obtain the maximum power output from PV array via MPPT, a Zeta converter is used .This system eliminates the phase current sensors and acquires fundamental frequency switching of VSI,which contributes in avoiding the power loss due to high frequency switching. No circuitry is required to control the PMBLDC motor. It is controlled via variable DC link voltage of VSI. It also presents a new idea to completely remove the dc link capacitor which is bulky and also increase the cost of motor. But this elimination results in torque ripple to arise at the output of motor. A ceramic capacitor and switch are used in place of dc link capacitor to miminimise the torque ripple. Simulation is performed using MATLAB/SIMULINK software and the results are presented.